First report of Lyme disease in Nepal. (10th January 2018) - Pun, Sher Bahadur; Agrawal, Sumit; Jha, Santoshananda; Bhandari, Lila Nath; Chalise, Bimal Sharma; Mishra, Abadhesh; Shah, Rajesh
Abstract : Introduction. Lyme disease is a tick-borne illness caused by the spirochete Borrelia burgdorferi and is widely reported in the USA, Central Europe, South East Asia and Latin America. Until recently, no scientific report regarding Lyme disease in Nepal had been published. Case presentation. A 32-year-old, previously healthy female visited the hospital with a history of joint pains, fatigue, neck stiffness, tingling sensation and headache. She was initially treated for typhoid fever, brucellosis and malaria, but did not show significant improvement. Doxycycline was prescribed empirically for 3 weeks for the treatment of suspected tick-borne illness. A two-tiered immunoglobulin laboratory testing confirmed Borrelia burgdorferi . She developed post-treatment Lyme disease syndrome after completion of antibiotic therapy. Conclusion. To the best of our knowledge, this is the first report of Lyme disease in Nepal and probably the first documented case of post-treatment Lyme disease syndrome in Asia. Lyme disease might have been overlooked in Nepal and, therefore, patients having clinical signs and symptoms similar to Lyme disease should not be disregarded in differential diagnosis.